118 Our people: sharing simulation learning. (15th December 2021) - Mooncey, Mumtaz; Potts, Laura; Gaynor, Edward; Ross, Alasdair; Simpson, Gabrielle
Abstract : Background: Simulation training is an invaluable educational activity and takes place regularly throughout the Trust. However, due to shift-working and often busy caseloads, it is not always possible for all members of staff to attend simulation sessions. As well as the important clinical teaching simulation training provides, there is also a wealth of non-technical learning to be gained, with potential for increased focus on Human Factors training. Aims: To create a standardised method for disseminating simulation learning to the wider multidisciplinary team. To increase the focus on Human Factors training during simulation. Methods: In conjunction with the established simulation programme, a template was created for anonymised written feedback, following the simulation session. This was one side of A4 which included: Aims & Objectives of the session Key Technical Learning Points Human Factors Feedback Links to Learning Resources/Guidelines Human Factors learning points were allocated a designated share of the immediate 'hot' debrief time following simulation, encouraging discussion from participants. All participants were assented for anonymised sharing of learning points following the session. This enabled the document to be shared with the wider multidisciplinary team. (Ethical approval was not required). Results: The simulation learning summary document was extremely well received. It enabled the valuable learning points from simulation to be shared much more widely than solely those present for the session. This was done in a number of departments, and the Gastroenterology department also shared the learning via a monthly newsletter. Human Factors learning points received unanimously positive feedback from participants using QR code feedback. Discussion/Conclusion: The importance of Human Factors has been highlighted through this approach to simulation training, and participants were noted to take on board feedback and apply it to their practice in future simulation sessions. A written document helps consolidate and share valuable learning.